Validity of the effective medium theory for modeling near-field thermal emission by nanowire arrays. (March 2021) - Zare, Saman; Pouria, Ramin; Edalatpour, Sheila
Highlights: Numerically exact simulations of near-field thermal emission by quartz nanowire arrays is reported. The Maxwell-Garnett and Bruggeman effective medium theories (EMTs) can only qualitatively predict near-field thermal emission by nanowire arrays when the array pitch over the observation distance is in the range of 1 and π. The Maxwell-Garnett EMT is slightly more accurate than the Bruggeman EMT. The EMT cannot capture the lateral variation of near-field thermal emission by nanowire arrays. Abstract: Nanowire arrays are promising man-made materials for tuning the spectrum and the magnitude of near-field thermal radiation. Near-field radiative properties of nanowire arrays are often studied using the effective medium theory (EMT). In this paper, we inspect the validity of the Maxwell-Garnett (MG) and Bruggeman (BR) EMTs for predicting near-field thermal emission by quartz and indium tin oxide (ITO) nanowire arrays. The near-field energy density predicted using the EMTs is compared with numerical simulations obtained using the thermal discrete dipole approximation. For quartz nanowire arrays, which support localized surface phonons in the infrared region, neither MG nor BR EMT can accurately predict the spectrum and the magnitude of near-field thermal emission even at distances, zo, greater than the array pitch, L over π. Based on the performed simulations, the EMT agrees the best with the T-DDA when 1 < L z o < π . It is also shown that MG EMT is slightly more consistent with numerical simulations than the BR EMT. For the ITO array, which does not support localized surface plasmons in the infrared region, the MG EMT provides an acceptable estimations of near-field thermal radiation. Finally, it is observed that near-field emission can vary by a factor of two in lateral directions which cannot be captured in the EMT.